2002
DOI: 10.1029/2002gl015321
|View full text |Cite
|
Sign up to set email alerts
|

Large‐amplitude internal wave generation in the lee of step‐shaped topography

Abstract: [1] Laboratory experiments show that as uniformly stratified fluid flows over a smoothly-varying step, two wave-like phenomena result: boundary-trapped lee waves, characterized by an undular shear layer downstream of the base of the step, and internal waves, which propagate vertically away from the step. The frequency of both types of waves is an approximately constant fraction of the buoyancy frequency. The frequency of internal waves is moderately smaller than lee waves if the step size is small but, if the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…h/w d , where w d is the downstream half-width of the obstacle. Sutherland (2002) illustrated how the first term can be eliminated with h/w d ≈ 0, but it seems plausible that the transition cannot be "infinitely" sharp: one should detect gradual (but certainly nonlinear) changes when h/w d approaches zero. This simple argumentation might be related with the observed anomaly in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…h/w d , where w d is the downstream half-width of the obstacle. Sutherland (2002) illustrated how the first term can be eliminated with h/w d ≈ 0, but it seems plausible that the transition cannot be "infinitely" sharp: one should detect gradual (but certainly nonlinear) changes when h/w d approaches zero. This simple argumentation might be related with the observed anomaly in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…He identified stationary lee-waves trapped in the wake of the obstacle and vertically-propagating internal waves of slightly different frequencies but of the same amplitudes. Sutherland (2002) concluded that the dynamics are governed by nonhydrostatic nonlinear effects. Note that his parameter range [U, N, H, h] was essentially the same as in our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both studies ignored the influence of internal waves upon separation and, conversely, ignored the impact of boundary layer separation upon internal wave generation. In experiments studying stratified flow over a step [3], vertically propagating waves and boundary-trapped lee waves were found to couple resonantly. The period of both was an approximately constant fraction of the buoyancy period.…”
Section: Introductionmentioning
confidence: 99%